The violent white dwarf merger scenario for the progenitors of Type Ia supernovae - Liu, D; Wang, B; Podsiadlowski, P; Han, Z (Oxford University Press, 2016)
Recent observations suggest that some Type Ia supernovae (SNe Ia) originate from the merging of two carbon-oxygen white dwarfs (CO WDs). Meanwhile, recent hydrodynamical simulations have indicated that the accretion-induced collapse may be avoided under certain conditions when double WDs merge violently. However, the properties of SNe Ia from this violent merger scenario are highly dependent on a particular mass-accretion stage, the so-called WD + He subgiant channel, during which the primary WD is able to increase its mass by accreting He-rich material from an He subgiant before the systems evolves into a doubleWD system. In this paper, we aim to study this particular evolutionary stage systematically and give the properties of violentWDmergers. By employing the Eggleton stellar evolution code, we followed a large number of binary calculations and obtained the regions in parameter space for producing violent mergers based on the WD + He subgiant channel. According to these simulations, we found that the primary WDs can increase their mass by ∼0.10-0.45M⊙ during the massaccretion stage. We then conducted a series of binary population synthesis calculations and found that the Galactic SN Ia birthrate from this channel is about 0.01-0.4 × 10-3 yr-1. This suggests that the violent WD mergers from this channel may only contribute to ∼0.3-10 per cent of all SNe Ia in our Galaxy. The delay times of violent WD mergers from this channel are ≥1.7Gyr, contributing to the SNe Ia in old populations. We also found that the WD + He subgiant channel is the dominant way for producing violent WD mergers that may be able to eventually explode as SNe Ia.